Dauru Hausabati al-Ma’ajim al-Arabiyyah: The Role of The Arabic Digital dictionary - Nanda Dzikrillah Pelealu; Sumiati Sumiati; Hermiwati Hermiwati (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
The purpose of this study is to discuss the importance of computerized Arabic dictionaries for today and the types of computerized Arabic dictionaries. This type of research uses library research with a qualitative approach method of descriptive analysis. From this study the researcher can conclude that digital dictionaries play an important role in helping individuals understand new vocabulary thanks to the efficiency and flexibility it offers compared to printed dictionaries. Digital dictionaries provide features such as multimedia, speed in searching, constant updates, and interactive features that help in learning languages effectively. There are several Arabic digital dictionary applications that have existed and developed, namely the Arabic-Indonesian Dictionary by Ristek Muslim, Al-Maany Arabic-Indonesian Dictionary, Al-Maany Arabic-Arabic Dictionary, Al-Kamus by Ustadz Firanda Andirja Official. For this reason, it can be said that computational Arabic dictionaries contribute significantly to improving the accessibility, efficiency, and experience of learning and using Arabic.